PROCEDURES OF FOREIGNIZING CULTURE- SPECIFIC- TERMS IN THE NOBLE QUR’AN - Ghada Rajeh Ayyad; Tengku Sepora Tengku Mahadi (INTERNATIONAL JOURNAL OF HUMANITIES, PHILOSOPHY AND LANGUAGES (IJHPL), 2024)
Due to the differences between cultures, translating terms that are related to a specific culture is a hard row to hoe. These terms are deeply rooted in culture. Therefore, it is almost impossible to find an equivalent for such terms. In fact, the task becomes more difficult in case of religious texts such as the Noble Qur’an. This problem has been a major focus of translation theorists and scholars. To solve such a problem, Venuti (1995) introduced the foreignization strategy that aims at transferring both the meaning and the culture of the source language to the target language. This strategy requires the translators to use some translation procedures to apply it. This paper tends to discuss the procedures used by the translators of the Noble Qur’an to foreignize culture-specific-terms.